Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

A method for quantifying feeding behavior of grass carp in outdoor ponds with complex backgrounds - Weiqiang Ni; Kang Wu; Lei Wang; Chenqing Zhang; Zequn Peng; Rong Tang; Zhangying Ye; Jian Zhao (Computers and Electronics in Agriculture, 2026)

Investigation of In-Situ Shear Failure Mechanism of Rock and Acoustic Emission Characteristics Using Discrete Element Method - Long Chen; Jian-jun Huang; Ze Yang; Shun-chuan Wu; Shang-rong Wu; Yu-song Zhao (Applied Geophysics, 2026)

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

Response characteristics of the symbiotic flocs system of bacteria and algae in treating Marine aquaculture wastewater with oxytetracycline - Tingting Tian; Hongwei Rong; Jingyin Wang; Lei Wang; Dongxu Wu; Jian Ma; Dengpan Qin (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

How does urban green infrastructure influence tourist loyalty: A moderated mediation model - Liangliang Rong; Kehui Wu; Liangru Tao; Xiangyu Meng; Jiayi Feng; Lixia Peng; Zhongjian Fang; Guoqiang Zhan; Jian Wang (Journal of Outdoor Recreation and Tourism, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Genetic basis of pedicellate spikelet masculinization in maize revealed by an advanced maize–teosinte population - Ruifan Bao; Xueying Wang; Junle Wu; Ting Liang; Xiya Hu; Pengxu Meng; Hang Mi; Peng Li; Sijia Yang; Zhiqin Liu; Siyu Lei; Jinyu Yang; et al. (Planta, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Bioinspired interfacial anchoring enables durable ultra-black photothermal coatings based on silica-coated carbon nanotubes - Jian Li; Yan Wang; Xiaolong Wu; Chao Li; De-Rong Sun; Peng Wang; Zimu Li; Xue-Qing Liu (Chemical Engineering Journal, 2026)

Integrating machine learning and prioritization to decipher the partitioning and risk of tire-derived chemicals in highly populated coastal regions - Nian-Nian Wu; Yuan Liu; Shan Liu; Ji-Xun Chen; Qin-Ge Zhou; Xiang-Rong Xu; Qing-Song Yang; Juan Ling; Jian-Liang Zhao (Water Research, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Metabolic engineering of Pichia pastoris for high-efficiency production of branched-chain amino acids -enriched single-cell protein - Cancan Dong; Kai Hong; Fan Wu; Yanfeng Wang; Youyan Rong; Xin Wu; Jian Zhang; Le Gao (Bioresource Technology, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

An intelligent nanotheranostic for size-driven integrated tumor radiosensitization and radioprotection - Mengting Gao; Yarong Jin; Xiaorui Song; Jian Zhang; Ajing Wu; Qiao Ye; Binyue Zhang; Jinxuan Li; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

A comprehensive review on tellurium extraction and recycling technologies from copper anode slime - Yuefeng Chen; Shixing Wang; Rong Zhu; Yihui Wu; Jiaxin Luo; Guowei Luo; Jian Liu; Libo Zhang (Chemical Engineering Journal, 2025)

Enhanced oxidation leaching of silver from zinc leaching residue via an electric field - Rong Zhu; Jianqiang Ye; Shixing Wang; Dawei Xiang; Yuefeng Chen; Yihui Wu; Guowei Luo; Jiaxin Luo; Chenxu Wang; Libo Zhang; Jian Liu (Chemical Engineering Journal, 2025)

Adipose-bone microenvironment precision-regulation nanoplatform: A visualized mild photothermal-enhanced osteogenesis strategy for osteonecrosis of the femoral head - Jinxuan Li; Mengting Gao; Yuhang Wang; Rong Dai; Qi Liu; Shutong Wu; Jian Zhang; Hua Wu; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Associations between plasma multi-metal exposure and mild renal impairment: Cross-sectional evidence of the potential mediating role of HDL-C in rural China - Kaisheng Teng; Qinyi Guan; Xiaoting Mo; Qiumei Liu; Lei Luo; Jiahui Rong; Tiantian Zhang; Wenjia Jin; Linhai Zhao; Songju Wu; Jiansheng Cai; Zhiyong Zhang; et al. (Toxicology and Applied Pharmacology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Association of multi-metal exposure with hyperuricemia in middle-aged and older adults: A cross-sectional study in rural Guangxi, China - Qinyi Guan; Kaisheng Teng; Qiumei Liu; Songju Wu; Lei Luo; Linhai Zhao; Jiahui Rong; Wenjia Jin; Tiantian Zhang; Mo Xiaoting; Cai Jiansheng; Zhiyong Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Triggered synergistic effect of Fe single atoms and tiny Co nanoparticles to enhanced oxygen electrocatalysis bifunctionality for zinc-air batteries - Jing Wu; Jian Rong; Chaohai Wang; Chaosheng Wang; Ning Fang; Yuzhe Zhang; Huaisheng Ao; Chao Jing; Yusuke Yamauchi; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Identification and segregation of two closely linked major QTLs for kernel row number in advanced maize–teosinte populations - Jixing Ni; Dengguo Tang; Zhengjie Chen; Sijia Yang; Xueying Wang; Zhiqin Liu; Wujiao Deng; Haimei Wu; Chong You; Jinchang Yang; Pengxu Meng; Ruifan Bao; et al. (Theoretical and Applied Genetics, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

High-performance hydrogel membranes with superior environmental stability for harvesting osmotic energy - Caiqin Wu; Rong Wu; Huan Zeng; Chenling Yao; Jialing Zhou; Guilong Li; Jian Wang (Chemical Engineering Journal, 2024)

Construction of large-aperture mesoporous silica spheres supported polyoxometalate heterogeneous catalysts and their high-efficiency for the ultra-deep desulfurization - Jia-Qi Wu; Lu-lu Ma; Zhuang-Zhuang Li; Xin Li; Si-Wen Li; Chang Li; Rong-Xi Li; Jian-She Zhao (Fuel, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Biochemical and Transcriptome Analysis Reveals Pigment Biosynthesis Influenced Chlorina Leaf Formation in Anoectochilus roxburghii (Wall.) Lindl - Xiu-Xian Ye; Yi-Quan Chen; Jian-She Wu; Huai-Qin Zhong; Bing Lin; Min-Ling Huang; Rong-Hui Fan (Biochemical Genetics, 2024)

Determination of tetrodotoxin in bivalve mollusks by hydrophilic interaction liquid chromatography-triple quadrupole mass spectrometry with internal standard calibration and its contamination in Zhejiang province, China - Ming-rong Qian; Hui-zhen Wu; Zeng-xuan Cai; Mei-jia Xu; Jian-long Han; Xiao-min Xu (Food Chemistry, 2024)

Introducing local-molecule trap in a cost-effective metal–organic framework for C2H2/CO2 separation - Xue-Qian Wu; Tao He; Peng-Dan Zhang; Jiamei Yu; Jian-Rong Li (Chemical Engineering Journal, 2024)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Current status, future prediction and offset potential of fossil fuel CO2 emissions in China - Jiaxi Cao; Jian Zhang; Ye Chen; Rong Fan; Lei Xu; Entao Wu; Yuan Xue; Junliu Yang; Yiming Chen; Bo Yang; Shuhong Wu (Journal of Cleaner Production, 2023)

Genome sequence of a Sobemovirus from the feces of Northern Pintail (Anas acuta) - Yu-Rong Wei; Xiao-Yun Mi; Jian-Yong Wu (Virus Genes, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Transformation of cognition from mechanical to biological aqueous outflow pump may be a breakthrough in solving the problem of intraocular pressure regulation in glaucoma - Shen Wu; Chen Xin; Wei Zhu; Yue Wan; Qing Sang; Rong Du; Jian Wu; Jin Wang; Ningli Wang (Science China Life Sciences, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Orange protein (DbOR) from the salt-tolerant green alga Dunaliella bardawil mediates photosynthesis against heat stress via interacting with DbPsbP1 - Ming-Hua Liang; Jv-Liang Dai; Shan-Rong Xie; Jing-Xuan Wu; Hao-Hong Chen; Jian-Guo Jiang (Algal Research, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Mechanical and microscopic properties of soil according to the rate of increase in pore water pressure - Zhao Duan; Zhen-Yan Li; Yan-Bin Wu; Bing Niu; Rong-Jian Shen (Soil and Tillage Research, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

Molecular evolution of GII.P17-GII.17 norovirus associated with sporadic acute gastroenteritis cases during 2013–2018 in Zhoushan Islands, China - Can Chen; Bing Wu; Hui Zhang; Ke-Feng Li; Rong Liu; Hong-Ling Wang; Jian-Bo Yan (Virus Genes, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Pericarp and seed of litchi and longan fruits: constituent, extraction, bioactive activity, and potential utilization - Xiang-rong Zhu; Hui Wang; Jian Sun; Bao Yang; Xue-wu Duan; Yue-ming Jiang (Journal of Zhejiang University-SCIENCE B, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Arctic Climate Changes Based on Historical Simulations (1900‒2013) with the CAMS-CSM - Ting Wei; Jian Li; Xinyao Rong; Wenjie Dong; Bingyi Wu; Minghu Ding (Journal of Meteorological Research, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Characterization of a new multifunctional beta-glucosidase from Musca domestica - Shu Zhang; Jian Huang; Rong Hu; Guo Guo; Xiaoli Shang; Jianwei Wu (Biotechnology Letters, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Adsorption behavior and mechanism of ibuprofen onto BiOCl microspheres with exposed {001} facets - Jian Li; Shiye Sun; Rong Chen; Tuqiao Zhang; Bangxing Ren; Dionysios D. Dionysiou; Zhejian Wu; Xiaowei Liu; Miaomiao Ye (Environmental Science and Pollution Research, 2017)

Leaf structure affects a plant’s appearance: combined multiple-mechanisms intensify remarkable foliar variegation - Yun-Shiuan Chen; Peter Chesson; Ho-Wei Wu; Shang-Hung Pao; Jian-Wei Liu; Lee-Feng Chien; Jean W. H. Yong; Chiou-Rong Sheue (Journal of Plant Research, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Role of immune tolerance in BALB/c mice with anaphylactic shock after Echinococcus granulosus infection - Qin Zhang; Jian-Rong Ye; Hai-Mei Ma; Jian-Jiang Wu; Tao Jiang; Hong Zheng (Immunologic Research, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Modification and simulation of Rhizomucor miehei lipase: the influence of surficial electrostatic interaction on enantioselectivity - Gang Xu; Xiao Meng; Lin-Jie Xu; Li Guo; Jian-Ping Wu; Li-Rong Yang (Biotechnology Letters, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

Introducing a salt bridge into the lipase of Stenotrophomonas maltophilia results in a very large increase in thermal stability - Jian-Ping Wu; Mu Li; Yong Zhou; Li-Rong Yang; Gang Xu (Biotechnology Letters, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Immobilization of trace metals by phosphates in contaminated soil near lead/zinc mine tailings evaluated by sequential extraction and TCLP - Wei-Hong Wu; Zheng-Miao Xie; Jian-Ming Xu; Fan Wang; Jia-Chun Shi; Rong-Bin Zhou; Zan-Fang Jin (Journal of Soils and Sediments, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Nitrogen transformations and balance in constructed wetlands for slightly polluted river water treatment using different macrophytes - Haiming Wu; Jian Zhang; Rong Wei; Shuang Liang; Cong Li; Huijun Xie (Environmental Science and Pollution Research, 2013)

Mapping of quantitative trait loci for oil content in cottonseed kernel - QUAMPAH ALFRED†; HAI YING LIU†; HAI MING XU; JIN RONG LI; JIAN GUO WU; SHUI JIN ZHU; CHUN HAI SHI (Journal of Genetics, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Fluorescence in situ hybridization on plant extended chromatin DNA fibers for single-copy and repetitive DNA sequences - Kun Yang; Hecui Zhang; Richard Converse; Yong Wang; Xiaoying Rong; Zhigang Wu; Bing Luo; Liyan Xue; Li Jian; Liquan Zhu; Xiaojia Wang (Plant Cell Reports, 2011)

Molecular characterization and expression patterns of Lbx1 in porcine skeletal muscle - Zhe Chao; Jian Wu; Rong Zheng; Feng-E. Li; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

QTL mapping for test weight by using F 2:3 population in maize - JUN-QIANG DING; JIN-LIANG MA; CHUN-RONG ZHANG; HUA-FANG DONG; ZHANG-YING XI; ZONG-LIANG XIA; JIAN-YU WU (Journal of Genetics, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Improvement of the CuZn-superoxide dismutase enzyme activity and stability as a therapeutic agent by modification with polysialic acids - Jian Rong Wu; Yi Lin; Zhi Yong Zheng; Chi Chung Lin; Xiao Bei Zhan; Ying Qiang Shen (Biotechnology Letters, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Arachnoid cell involvement in the mechanism of coagulation-initiated inflammation in the subarachnoid space after subarachnoid hemorrhage - Zhao-liang Xin; Xiao-kang Wu; Jian-rong Xu; Xi Li (Journal of Zhejiang University-SCIENCE B, 2010)

Research of the ATPase’s rotation catalysis stochastic transition dynamics - Yan Zheng; Ming-Jian Yang; Wei-Xia Wu; Kun Yu; Ying-Rong Han; Yong Zhan; Yan-Bin Huang (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Relationship between transmembrane signal transduction pathway and DNA repair and the mechanism after global cerebral ischemia-reperfusion in rats - Rong-Liang Xue; Jia-Xuan He; Ning Wang; Feng-Zhen Yao; Jian-Rui Lv; Gang Wu (Neuroscience Bulletin, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Involvement of voltage-gated K+ and Na+ channels in gastric epithelial cell migration - William Ka Kei Wu; Gui Rong Li; Tak Ming Wong; Jian Ying Wang; Le Yu; Chi Hin Cho (Molecular and Cellular Biochemistry, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Isolation and characterization of a human putative receptor protein kinase cDNA STYK1* - Xin Ye; Chaoneng Ji; Qingshan Huang; Chao Cheng; Rong Tang; Jian Xu; Li Zeng; Jianfeng Dai; Qihan Wu; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Mapping of leaf and neck blast resistance genes with resistance gene analog, RAPD and RFLP in rice - Jie-Yun Zhuang; Wen-Bin Ma; Jian-Li Wu; Rong-Yao Chai; Jun Lu; Ye-Yang Fan; Min-Zhong Jin; Hei Leung; Kang-Le Zheng (Euphytica, 2002)

Immobilization of lipase by salts and the transesterification activity in hexane - Wang Pu; Yang Li-rong; Wu Jian-ping (Biotechnology Letters, 2001)